Impact of County Health Rankings on Nationwide Liver Transplant Outcomes. Issue 11 (November 2021) - Niazi, Shehzad K.; Vargas, Emily; Spaulding, Aaron; Crook, Julia; Keaveny, Andrew P.; Schneekloth, Terry; Rummans, Teresa; Taner, C. Burcin
Abstract : Background: There is limited information concerning whether social determinants of health affect postliver transplant (LT) outcomes. This study aims to understand to what extent the health of LT recipients' counties of residence influence long-term LT outcomes. Methods: We used the United Network for Organ Sharing data to identify adult LT recipients transplanted between January 2010 and June 2018. Patient-level data were matched to county-level County Health Ranking (CHR) data using transplant recipient zip code, and nationwide CHRs were created. Mixed-effects Cox proportional hazards models were used to examine associations between CHRs and graft and patient survival post-LT. Results: Health outcomes rank was significantly associated with posttransplant graft and patient survival, with worst tertile counties showing a 13% increased hazard of both graft failure and patient mortality compared to the best tertile counties. Conclusions: Although county health is associated with LT outcomes, it also appears that LT recipient selection is effective at mitigating major disparities based on county of residence and helps yield equitable outcomes in this respect. Abstract : Supplemental Digital Content is available in the text.